AN ECONOMIC ORDER QUANTITY MODEL FOR LOTS CONTAINING DEFECTIVE ITEMS WITH REWORK OPTION - Öztürk, Harun; Eroglu, Abdullah; Lee, Gyu M (International Journal of Industrial Engineering: Theory, Applications and Practice, 2016)
In a manufacturing system, it is unavoidable that defective items are produced. A portion of these defective items are reworkable and often lead to extra profits by reworking them. In order to determine their effects on the total profit, an economic order quantity model for lots containing defective items with existence of shortages when the rework option available is proposed. The proposed model determines the economic order quantity and backorder quantity for a single item in an ordering system. It is assumed that a 100% inspection process is performed to separate good and defective items in each ordered lot. The defective items consist of imperfect quality, scrap and reworkable items. The rework can be done only to reworkable items to make good or scrap items. A numerical example is provided to show the effects of the rework option in the proposed model. In order to determine whether the cost of rework is justifiable, the proposed model is compared with the one including only imperfect quality and scrap items with existence of shortages. Finally, sensitivity analysis on some parameters in the proposed model is carried out.